EFFECT OF FEEDING DIFFERENT LEVELS OF GUAR MEAL ON HEALTH AND CARCASS CHARACTERISTICS OF LOCAL GOAT KIDS (Indian Journal of Animal Production and Management, 2016)
A feeding trial was conducted to evaluate the effect of guar meal, an unconventional protein source on  health and carcass characteristics of local kids. 3 months old kids divided into three equal groups (control,  T1 and T2) randomly were fed concentrate mixture containing ground nut cake (control) while in T1 and  T2, ground nut cake was replaced with guar meal at 50 and 100 %, respectively. Significantly (P
Keywords: Carcass characters; Guar meal; Histopathology; Unconventional feed